SOBA JAGUNG KUAH ASAM DINGIN DENGAN SUBSTITUSI TEPUNG JAGUNG - Badraningsih Lastariwati, Dwi Apriliyanto (Prosiding Pendidikan Teknik Boga Busana, 2020)
Corn is the second staple food after being successful One of the ways to process corn in Indonesia so that it can be more widely accepted by society is by processing corn into various processed foods. Soba Jagung is a processed noodle that modifies the main ingredients which are originally from wheat flour research and development of this product using the type of research and development called R&D. materials and research tools in the form of urang sensory test form validation 1 and validation 2 as well as detailed product testing forms conducted by experienced parties. sensory test is used to see the characteristics of the preferred test product used to see the acceptance of the product as a result of sensory testing is that the product can be accepted to test the product acceptance from sensory test results and the preference that the product is well received by the public.